2004
DOI: 10.1016/j.compstruct.2003.09.050
|View full text |Cite
|
Sign up to set email alerts
|

Efficient modelling of delamination buckling in composite cylindrical shells under axial compression

Abstract: Composite cylindrical shells and panels are widely used in aerospace structures. These are often subjected to defects and damage from both in-service and manufacturing events.Delamination is the most important of these defects. This paper deals with the computational modelling of delamination in isotropic and laminated composite cylindrical shells. The use of three-dimensional finite elements for predicting the delamination buckling of these structures is computationally expensive. Here combined double-layer a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
25
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 23 publications
1
25
0
Order By: Relevance
“…Four different materials [16,17] are used to investigate the effect of engineering constants on the optimum shape design of the components. Every component is being treated as a lamina that has four engineering constants E 1 , E 2 , G 12 and  12 with a lamina orientation angle of zero.…”
Section: Numerical Resultsmentioning
confidence: 99%
“…Four different materials [16,17] are used to investigate the effect of engineering constants on the optimum shape design of the components. Every component is being treated as a lamina that has four engineering constants E 1 , E 2 , G 12 and  12 with a lamina orientation angle of zero.…”
Section: Numerical Resultsmentioning
confidence: 99%
“…The study on instability analysis of delaminated composite cylindrical shells subject to axial compression, external pressure and bending, either applied individually or in combination [21][22][23] showed that the SERR was more convenient to be used for the prediction of crack growth and fracture of delaminated composite structures. Here it is shown that although the SIF is of fundamental importance in the prediction of brittle failure using linear elastic fracture mechanics, the SERR for cracked anisotropic meshes has been found to be more convenient for these predictions.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of delaminations leads to a reduction in the overall buckling strength of the structure [3][4]. For the past two decades analytical and numerical analyses have been carried out by many researchers to analyse delaminated composite structures, considering their buckling and post-buckling behaviour [5][6].…”
mentioning
confidence: 99%
“…[17][18][19][20][21][22][23]. Due to its mathematical complexity and modelling, very limited information on the subject of delamination buckling of cylindrical shells and panels is currently available [3][4][24][25][26][27][28][29][30][31][32][33]. The most comprehensive analytical study is by Simitses et al [25][26][27].…”
mentioning
confidence: 99%
See 1 more Smart Citation